Advances in applied microbiology. - Gadd, Geoffrey M.; Sariaslani, Sima (Advances in applied microbiology ;, 2019)
'Advances in Applied Microbiology, Volume 107,' continues the comprehensive reach of this widely read and authoritative review source in microbiology. Users will find invaluable references and information on a variety of areas, with this updated volume including chapters covering the roles and applications of siderophores, biological oxidation of iron sulphides, production of biomass and biofuel feedstocks from microalgae, advances in the microbial ecology of biohydrometallurgy, bacterial synthesis of Se nanoparticles, and siderophores in environmental research, amongst other discussions. --